Typology analysis and adaptive capacity of commercial gardening farmers to climate change in peri-urban areas along the coastal area of Benin (West Africa) - Ahouangan, Bidossessi Syntiche Chiméi Mérimée; Koura, Bossima Ivan; Lesse, Armel Dodji Paolo; Ahoyo, Carlos Cédric; Toyi, Scholastique Mireille; Vissin, Expédit Wilfrid; Houinato, Marcel Romuald Benjamin (Frontiers in Sustainable Food Systems, 2024)
The coastal environment represents a special site for human and economic activities. The population growth in this area has led to strong urbanization and, therefore, to the establishment of small-scale vegetable farms to feed the growing urban and peri-urban populations. This is an opportunity for youth employment and reduce poverty as this activity generates reliable incomes. However, in recent years, climatic changes and rapid urbanization have influenced agricultural activities in this area. The aim of this study was to characterize market gardening systems along the coastal area of Benin and understand farmers' perceptions and adaptation strategies in response to the ongoing environmental changes. Data was collected from 130 farms using individual semi-structured questionnaires. A principal component analysis (PCA), K-Mean multivariate classification and statistical inference were used for data analysis. Three farm groups were identified from the hierarchical bottom-up classification: modern coastal farms (MCF, 59,24 %), small-scale intra-urban farms (SIF, 35,38 %) and traditional comanaged lowland farms (TCF, 5,38 %). The perceived environmental changes were mainly temperature increases, strong winds and migration to another farmland. The criteria differentiating the groups were strong winds and variation in the start date of the rains (P˂0.05).According to current strategies farmers in groups 1 and 2 preferred crop diversification, those in group 3 moved their farms. Future strategies range from the early sale of crops to the use of modern watering equipment to the cessation of farming. Thus, sustainable farm management requires the involvement of decentralized structures and local stakeholders to maintain the livelihoods of local populations.